Examination of the need for additional pharmaceutical services and selected elements of pharmaceutical care in Poland - pilot study - Natalia Wrzosek; Aleksandra Chlebowska; Dominika Polakowska; Jagoda Miszewska; Sara Kowalska; Oliwia Dobbek; Agnieszka Ewa Zimmermann (Polish Pharmaceutical Society, 2021)
Background: A pharmacy is a healthcare facility where authorised personnel provides, pharmaceutical services. In accordance with the implementation of the Act on the Pharmacy Profession from April 16, 2021 in Poland, pharmaceutical care is defined as a health service provided. Due to new regulations, pharmacists were given wider permissions to provide additional pharmaceutical services, some diagnostic tests, as well as other healthcare services. Aim oft the study: Study aimed to assess the level of the patients' need for additional pharmaceutical services and selected elements of pharmaceutical care accessible in community pharmacies in Poland. In addition, respondents were also asked to provide a valuation of the described services. Moreover, study aimed to assess of the level of respondents' knowledge about pharmaceutical care as well as their needs and level of satisfaction related to the service of dispensing medicinal products, in particular regarding medical information provided by pharmacy professional staff. Materials and methods: Study used an anonymous online questionnaire as a tool to obtain the records of 145 patients. Results: No more than half of the respondents think that they receive satisfactory information about medicines from the pharmacy's professional staff. However, nearly 60% of respondents admit that they feel the need to analyze their drugs for interactions. Many patients are unfamiliar with the term "pharmaceutical care". Most of the study group would like to use the blood pressure measurement service along with the interpretation of the result, a Medical Use Review and instructions on how to use the inhaler. Slightly less, but still very popular, were: blood glucose measurements, preparation of individual drug packaging system and a review of the overview of the home first aid kit. The respondents valued the presented services low, often indicating that they should be free of charge. Conclusion: Polish patients have poor knowledge about the possibilities of pharmaceutical care by a pharmacist. Nevertheless, they show interest in potential additional services. The low valuation of services and benefits in the eyes of the patient indicates the need for reimbursement from the NHF budget.